Wali Nikah dalam Perspektif Pancasila dan Hukum Islam: Konflik dan Konvergensi: Marriage Guardians in the Perspective of Pancasila and Islamic Law: Conflict and Convergence - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Habib Zuhud Siswoyo; Muhammad Nurhidayat; Muhammad Bagus Wijayakusuma (DIRASAH: Jurnal Kajian Islam, 2025)
The study of marriage guardians in Islamic law and Pancasila in Indonesia is particularly relevant, given that the majority of Indonesia's population is Muslim and Pancasila is the basis of the state. In Islamic law, the marriage guardian - usually a father or male relative - plays an important role as a condition of a valid marriage, with validity dependent on the guardian's consent as a protector of women's rights. In contrast, Pancasila emphasizes social justice and gender equality, which raises the question of how the role of the marriage guardian can be harmonized with the principles of Pancasila. This research uses a normative juridical approach and comparative law method to analyze the regulation of marriage guardians in Islamic law and the influence of Pancasila on its application in national law, including in Law No. 1 of 1974 and the MUI fatwa. Case studies of marriages in Indonesia show conflicts between the authority of the guardian and the will of the woman, but also attempts at legal convergence for a more equitable solution. The research concludes that the integration of Islamic legal principles and Pancasila requires a comprehensive approach, considering Indonesia's plural social and cultural context. The results of this research are expected to assist in the development of marriage law that is inclusive and responsive to the dynamics of society.